2020
DOI: 10.3390/ani10091521
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Hepatitis E Virus Seroprevalence in Domestic Pigs and Wild Boar in Bulgaria

Abstract: (1) Background: Hepatitis E virus (HEV) is a causative agent of acute viral hepatitis, predominantly transmitted by the fecal–oral route. In developed countries, HEV is considered to be an emerging pathogen since the number of autochthonous cases is rising. Hepatitis E is a viral disease with a proven zoonotic potential for some of its genotypes. The main viral reservoirs are domestic pigs and wild boar. Consumption of undercooked meat, as well as occupational exposure, are key factors for the spread of HEV. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 55 publications
3
40
0
Order By: Relevance
“…We supposed that EBS are more likely to become infected with HEV from domestic pigs. HEV seropositivity among domestic pigs in those districts is high, around 77.14-80.0% (slaughter-aged pigs, 6 months old) [7]. The HEV seroprevalence in wild boars in those districts has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We supposed that EBS are more likely to become infected with HEV from domestic pigs. HEV seropositivity among domestic pigs in those districts is high, around 77.14-80.0% (slaughter-aged pigs, 6 months old) [7]. The HEV seroprevalence in wild boars in those districts has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, a detailed seroprevalence study of HEV infection in pigs from southern Bulgaria documented an overall HEV seroprevalence of 60.3% (217 of all 360 tested sera) [6]. Takova et al, reported that 4 of the 32 meat juice samples from Bulgarian wild boar were positive for anti-HEV IgG antibodies [7]. The study of these authors had several important limitations: the research included a relatively small number of wild boars (n = 32), and information regarding their age and sex were not recorded.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, investigations performed in swine herds revealed seroprevalences estimated between 30% and 100% [14][15][16][17][18][19][20][21][22][23] with molecular detection rates of 0.9% to 87.5% [24][25][26][27][28][29][30][31][32][33]. Similarly, epidemiological studies performed in wild boar populations reported antibody detection rates ranging from 12.5% to 57.4% and molecular prevalence of 0.3% to 68.2% [12,19,[34][35][36][37][38]. Transmission from deer to humans has also been described [39,40], although they mostly undergo spill-over HEV infections in contaminated habitat shared with wildlife reservoirs [12,41].…”
Section: Introductionmentioning
confidence: 99%
“…In developed counties, in the past decade, a number of autochthonous cases of HEV infection has been reported, and evidence for zoonotic transmission has been discovered [ 4 ]. The main HEV reservoirs are domestic pigs and wild boar [ 5 , 6 ]. Occupational exposure, as well as consumption of undercooked pork meat, are key factors for the spread of HEV in Europe [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%